Why do Chinese High School Graduates Choose Sino-Foreign Cooperative Universities? A Grounded Theory Approach - Nan Zhou; Qiang Li; Yanbo Zhang (SAGE Open, 2024)
Sino-foreign cooperative universities (SFCU) represent the advanced manifestation of transnational education in China and has profoundly shaped the country’s higher education landscape. Despite the tremendous development of SFCUs, there is limited research on the motivations and driving factors of students choosing to study at SFCUs. To bridge this research gap, this study employs the grounded theory approach to examine why Chinese high school graduates choose SFCUs as study destinations. This study reveals that Chinese students’ choice of SFCUs results from personal considerations, institution-level characteristics, and social contexts. A theoretical framework is further proposed to better understand Chinese students’ motivations behind their choice to SFCUs. We also draw theoretical contributions on students’ mobility and marketing strategies that attract Chinese students to study at SFCUs with the findings.